Educator perspectives on integrating climate change and environmental sustainability into occupational therapy education. - Santos, Audi Q; Nepveux, Denise M; Richardson, Elizabeth; Hood, Tyler; Murdock, Cameron; Mokhtar, Sina (Work, 2025)
Background: Climate change has been identified as the biggest threat to global public health. 1 Despite the clear connection between negative health outcomes and anthropogenic climate change, there are few guidelines for curricular inclusion within healthcare education, including occupational therapy (OT). However, the World Federation of Occupational Therapists has emphasized the importance of sustainability, 2 and the American Occupational Therapy Association published a policy asserting the profession's commitment to addressing these topics. 3 Objective: This study explored the perspectives of OT educators in the United States on the relevance, importance, and feasibility of integrating climate change and environmental sustainability into OT education programs. Methods: An online Qualtrics survey was distributed, with 64 respondents across the United States. Descriptive and inferential statistics were conducted to determine relationships between respondent responses to question pairs. Qualitative responses underwent thematic analysis. Results: Most educators acknowledged the relevance and importance of addressing climate change and environmental sustainability. Several barriers hindered implementation, including an already overloaded curriculum with a lack of explicitly related Accreditation Council for Occupational Therapy standards, limited time, a lack of awareness of how climate change and environmental sustainability fit into OT programs, and skepticism about climate change as relevant to OT practice. Conclusions: The findings indicate varied perspectives among US-based OT faculty. They suggest a need for educational resources that link climate change and environmental sustainability to health, occupation and other core tenets of OT and offer strategies for integrating this content into OT education.